2019
DOI: 10.3390/metabo9100225
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome and Metabolic Profiling Analysis of Buckwheat (Fagopyrum Tataricum (L.) Gaertn.) under Salinity Stress

Abstract: Tartary buckwheat (Fagopyrum tataricum (L.) Gaertn.) is a nutritional crop, which has high flavonoid content. However, buckwheat is a salt sensitive glycophyte cereal crop and the growth and grain yield of buckwheat are significantly affected by soil salinity. In this study, we performed a comprehensive analysis of the transcriptome and metabolome of salt treated-buckwheat to understand the effects of salinity on buckwheat. A total of 50,681,938 clean reads were acquired from all samples. We acquired 94,950 un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 82 publications
(127 reference statements)
2
28
0
Order By: Relevance
“…Similar to that which occurred in the present study, Liu et al [66] analyzed switchgrass under drought stress and found a large amount of AA and OA accumulation. Metabolomic analysis of buckwheat under salt stress also led to the same conclusion [49]. This suggests that plants may first rearrange OAs and AAs in response to salt stress [8].…”
Section: Oas Are Correlated With Salt Stressmentioning
confidence: 64%
See 1 more Smart Citation
“…Similar to that which occurred in the present study, Liu et al [66] analyzed switchgrass under drought stress and found a large amount of AA and OA accumulation. Metabolomic analysis of buckwheat under salt stress also led to the same conclusion [49]. This suggests that plants may first rearrange OAs and AAs in response to salt stress [8].…”
Section: Oas Are Correlated With Salt Stressmentioning
confidence: 64%
“…Some studies have indicated that phenylpropane biosynthesis is related to flavonoid and lignin synthesis, which can improve the osmoregulatory effect of Fraxinus mandshurica [48]. Ma et al reported similar conclusions with respect to buckwheat [49]. Therefore, the accumulation of Asc, apigenin-7-glucoside and luteolin may be involved in the salt response of plants.…”
Section: Flavonoids Are Correlated With Salt Stressmentioning
confidence: 91%
“…The presence and the development of phenolic compounds inuence their formation and stability, as well as the environmental factors or treatments. 10,19 The presence of procyanidins, among other polyphenols, lead to the health application of different parts of buckwheat, contributing to the initiation of many authors of buckwheat as a functional food. 24,25 Overall, the obtained results for 'Novosadska' buckwheat variety showed the similar polyphenols and prominent antioxidant capacity which were also reported by Kiprovski et al 23 Following the polyphenolic prole through different parts of buckwheat, it can be used for further investigations of the path and mechanism of the action of polyphenols.…”
Section: Phenolic Prolementioning
confidence: 99%
“…Therefore, metabolomics has potential to target many subjects for applications across several fields, such as chemotaxonomy, nutrition, pharmacology, and personalized medicine [7][8][9]. In plant science, metabolomics has been adopted to study not only the metabolite profiles of different crops or medicinal plants but also the taxonomic or biochemical differences of plant species grown in different ecotypes [5] or to trace the response of the metabolites under biotic/abiotic stimuli and plant adaptation [10]. Other applications include studying the difference between wild and domesticated or transgenic plants, crop improvement [11], biosynthesis pathway elucidation, correlation between metabolic markers and biological activity of medicinal plants [12], quality control of herbal preparations, and others [13].…”
Section: Introductionmentioning
confidence: 99%